CHALLENGES IN DIAGNOSING CHILDHOOD GINGIVITIS - Evangelista, Maria Gabrielly Soares; de Lima, Jaqueline Possas Rocha Valle; Bonifácio, Ricardo Furtado Cortês; Bettero, Fernanda Castelo Branco Santos; Vaz, Micaele de Almeida (Seven Editora, 2026)
Plaque-induced gingivitis is highly prevalent in childhood, but early and accurate diagnosis in pediatric patients faces significant challenges. Limitations include the subtlety of clinical signs, low patient cooperation, and variability in the inflammatory response across stages of dental development. Diagnosis should be multifactorial, integrating risk factors such as dietary habits (sugar consumption vs. protective dairy proteins) and socioeconomic determinants (daycare attendance, birth order). In addition to being a local condition, high levels of gingivitis in childhood serve as a predictive marker for metabolic diseases, such as type 2 Diabetes Mellitus, in adulthood. To overcome the limitations of traditional clinical methods, standardization of screening protocols and the adoption of innovative technologies (electronic probes and PCR tests) are recommended, aiming for a comprehensive and individualized approach that links oral health to the child’s systemic well-being.